Satu Dekade Perkembangan Surat Berharga Syariah Negara (SBSN) di Indonesia: Analisis Peluang dan Tantangan - Paripurna, Danial; Hidayat, Rahmat; Saharuddin, Desmadi (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
This paper examines the development of State Sharia Securities (Surat Berharga Syariah Negara/SBSN) in Indonesia over the past decade, focusing on the opportunities and challenges faced in its implementation. SBSN, or sovereign sukuk, is a Sharia-compliant financial instrument issued by the government to support the financing of the State Budget (APBN) and to stimulate the growth of the Islamic financial market. Since its first issuance in 2008, SBSN has shown significant growth in terms of investor numbers, issuance value, and product diversification. The government has developed various sukuk schemes including Green Sukuk and Mudharabah Sukuk to fund strategic and sustainable development projects. This paper also highlights ongoing challenges such as dependence on budget deficits, limited underlying assets, and the need for inter-agency coordination. Nevertheless, supported by strong regulatory frameworks and Sharia rulings, SBSN has great potential to become a key instrument in inclusive and Sharia-compliant development financing.